Cost-effectiveness of referral for generic care or problem-solving treatment from community mental health nurses, compared with usual general practitioner care for common mental disorders: Randomised controlled trial. - Kendrick, T; Simons, L; Mynors-Wallis, L; Gray, A; Lathlean, J; Pickering, R; Harris, S; Rivero-Arias, O; Gerard, K; Thompson, C (2006)
BACKGROUND: UK general practitioners (GPs) refer patients with common mental disorders to community mental health nurses. AIMS: To determine the effectiveness and cost-effectiveness of this practice. METHOD: Randomised trial with three arms: usual GP care, generic mental health nurse care, and care from nurses trained in problem-solving treatment; 98 GPs in 62 practices referred 247 adult patients with new episodes of anxiety, depression and life difficulties, to 37 nurses. RESULTS: There were 212 (86%) and 190 (77%) patients followed up at 8 and 26 weeks respectively. No significant differences between groups were found in effectiveness at either point. Mean differences in Clinical Interview Schedule - Revised scores at 26 weeks compared with GP care were -1.4 (95% CI -5.5 to 2.8) for generic nurse care, and 1.1 (-2.9 to 5.1) for nurse problem-solving. Satisfaction was significantly higher in both nurse-treated groups. Mean extra costs per patient were 283 pound (95% CI154-411) for generic nurse care, and 315 pound (183-481) for nurse problem-solving treatment. CONCLUSIONS: GPs should not refer unselected patients with common mental disorders to specialist nurses. Problem-solving should be reserved for patients who have not responded to initial GP care.